Proteome profiling of enzalutamide‐resistant cell lines and serum analysis identified ALCAM as marker of resistance in castration‐resistant prostate cancer. Issue 8 (21st June 2022) - Csizmarik, Anita; Keresztes, Dávid; Nagy, Nikolett; Bracht, Thilo; Sitek, Barbara; Witzke, Kathrin; Puhr, Martin; Tornyi, Ilona; Lázár, József; Takács, László; Kramer, Gero; Sevcenco, Sabina; et al.
Abstract: Enzalutamide (ENZA) is a frequently used therapy in metastatic castration‐resistant prostate cancer (mCRPC). Baseline or acquired resistance to ENZA have been observed, but the molecular mechanisms of resistance are poorly understood. We aimed to identify proteins involved in ENZA resistance and to find therapy‐predictive serum markers. We performed comparative proteome analyses on ENZA‐sensitive parental (LAPC4, DuCaP) and ‐resistant prostate cancer cell lines (LAPC4‐ENZA, DuCaP‐ENZA) using liquid chromatography tandem mass spectrometry (LC‐MS/MS). The top four most promising candidate markers were selected using bioinformatic approaches. Serum concentrations of selected markers (ALCAM, AGR2, NDRG1, IDH1) were measured in pretreatment samples of 72 ENZA‐treated mCRPC patients using ELISA. In addition, ALCAM serum levels were measured in 101 Abiraterone (ABI) and 100 Docetaxel (DOC)‐treated mCRPC patients' baseline samples. Results were correlated with clinical and follow‐up data. The functional role of ALCAM in ENZA resistance was assessed in vitro using siRNA. Our proteome analyses revealed 731 significantly differentially abundant proteins between ENZA‐sensitive and ‐resistant cells and our filtering methods identified four biomarker candidates. Serum analyses of these proteins revealed only ALCAM to be associated with poor patient survival. Furthermore, higher baseline ALCAM levels were associated with poor survival in ABI‐ but not in DOC‐treated patients. In LAPC4‐ENZA resistant cells, ALCAM silencing by siRNA knockdown resulted in significantly enhanced ENZA sensitivity. Our analyses revealed that ALCAM serum levels may help to identify ENZA‐ and ABI‐resistant patients and may thereby help to optimize future clinical decision‐making. Our functional analyses suggest the possible involvement of ALCAM in ENZA resistance. What's new?: Over the years, many new treatments have come on the market for metastatic castration‐resistant prostate cancer, including enzalutamide, an androgen receptor inhibitor with multiple mechanisms of action. Still, patients often develop resistance. Here, the authors used proteome analysis to identify proteins that contribute to enzalutamide resistance. By comparing protein expression in cells sensitive or resistant to enzalutamide, they created a list of 731 proteins of interest, which they later narrowed down to four potential biomarkers. Only ALCAM was associated with poor patient survival. Silencing ALCAM expression, they found, increased enzalutamide sensitivity.